Fatores de influência nas atitudes de consumidores de serviços em relação às práticas de responsabilidade social corporativa - Silva, Suzana Ribeiro da (2014)
This study aimed to understand how the attitudes of consumers of services configures in relation to the practices of Corporate Social Responsibility, by discovering which are the factors that influence these attitudes in tourism and leisure sector. Recent studies presented in this paper (CARVALHO et al., 2010; KOLODINSKY et al., 2010; KOLKAILAH et al., 2012; ROMANI et al., 2013) with a focus toward understanding the relationship between performance of companies and their consequences on perception of the target audience, show us that the theme of this research is current and relevant. The literature review has been structured with in order to discuss the elements that comprise the Social Responsibility, also entering the social responsibility of the consumer, to reflect on the attitudes of consumers in relation to business practices in general, and to analyze the attitudes towards Corporate Social Responsibility. Regarding the methodological procedures, the study was developed based on the research of the type of experiment that had the instrument model, a questionnaire containing propositions about the theme Corporate Social Responsibility, where stimuli were offered in the form of scenarios to verify the influence of the constructs selected about the attitude of consumers. The research sample consisted of residents of the state of Paraiba and Pernambuco, which could respond about companies operating in the tourism and leisure industry, specifically restaurants. The phase of data analysis included a descriptive analysis of the constructs through exploratory factor analysis with measurement of multiple items and measurement for a single item, an analysis of the variables Socially Responsible Consumer through a procedure of grouping; and analysis by cause, cost and a cross assessed using the parametric technique ANOVA and the non-parametric technique Kruskal-Wallis. The results indicated that the variables 'shared values', 'review of decision', 'admiration of the action', 'company image', 'predisposition to loyalty' and 'perception of opportunism', can be considered equally influencing the attitudes of persons in respect of CSR practices and that, statistically, there are no significant differences between stimuli by type of question and the absence or presence of cost. The research contributes to the area as far as it considers the view of the consumer within the theme of Social Responsibility, investigates consumer off-axis from developed countries and helps society understand that, for service consumers, any social cause adopted by a business will be evaluated, even if that cause is associated with a cost.